THE EFFECT OF MARKET ORIENTATION AND DISTRIBUTION CHANNELS ON MARKETING PERFORMANCE (Study on SMEs in the metal industry in Ngingas Waru Village) - Ahnaf Manaf; Widyastuti (Lavish Opulent Education, 2024)
MSMEs play a vital role in Indonesia's economy, contributing approximately 61% to the national GDP. The processing industry sector leads with an average turnover of 28.25% or 450 billion Rupiah. Ngingas Village, a hub for metal industry MSMEs since 1930, is known as the